Research of vulnerabilities database for parametrization of markov models of availability web-resources - Ponochovniy, Yu. L.; Rohochyi, S. Yu.; Sharai, O. I.; Knurenko, V. O.; Voronianskyi, V. S. (Systems and Technologies, 2019)
In this paper we consider issues of obtaining information from open data-bases of vulnerabilities and the creation of excerpt according to several criteria. The relevance of the topic is due to the need to ensure the parameterization of samples. Simulation helps increase the likelihood of detecting a vulnerability be-fore it is used by attackers. The issues of assessing the parameters of vulnerabili-ties of web resources are considered. These parameters are used as input in Mar-kov availability models. Availability is included in the set components of infor-mation security (confidentiality, integrity, availability). The article discusses the relationship between databases of vulnerabilities. The relationships between the CVE database and other open and paid reposito-ries are analyzed. Analyzed the current state of relations (uplink or downlink). The focus is on issues of updating the information given in open databases. The activity of the database, their openness, paid access or the possibility of trial / limited use are determined. For processing, information from the NVD vulnerability database in the form of archived XML files was obtained and refined. The following parameters were used as input parameters for Markov models: the intensity of the manifesta-tion of vulnerabilities and the criticality of the attack. The calculations of the in-tensity of the availability of vulnerabilities of Apache family of web servers based on samples for 2015 and 2016 are given. Attention is paid to the specification of the time of fixation of vulnerabilities in the database and the formation of samples based on a set of selection criteria from the open bases of vulnerabilities of NVD and CVE. The results of the study showed that in 2016, new vulnerabilities from the sample were recorded 3.23 times faster, but at the same time, their criticality de-creased by 3 % on average. The tendency of gradual growth of interest to net-work software products, in particular Apache web servers, is confirmed. To speed up and more convenient excerpt creation, it is advisable to deve-lop software that automatically creates the necessary excerpte after selecting the formation criteria. Also, to improve the results of the study, it is necessary to re-fine the vulnerability information in several open bases.